PENINGKATAN HASIL BELAJAR KIMIA MATERI SENYAWA HIDROKARBON SISWA SMAN 1 KALIWUNGU DENGAN METODE ”TUBA ASYIK” (Universitas Negeri Semarang, 2013)
The background of this study was the reality that the understanding of students in class X of SMAN 1 Kaliwungu about Hydrocarbon compounds is still very low. Learning method that has been done was the discussion of information and exercises. Students’ attention was initially 100%, but weakened after a such period and just when students did exercises, they seemed to lose of desire to learn. The change of teaching methods used was attempted by using the method of Tuba Asyik, the method of peer tutor combined with the fun games. This action research consisted of two cycles, each of which had a step of plan-action-observation-reflection. The analysis used was a qualitative and quantitative analysis, while the validation of the data used was triangulation. The percentage of attendance of students in Cycle I and Cycle II was 100%. The number of students who are enthusiastic about taking on the learning process was 65% PreCycle, Cycle I was 90%, in Cycle II was 92.5%. Classical Thoroughness of Learning in Cycle I was 78% and that in Cycle II was 85%. These figures showed that Tuba Asyik method was an appropriate and effective mthod to improve student learning outcomes in hydrocarbon compound topic.Keywords: TUBA Asyik Method